2005
DOI: 10.3390/ijerph2005010014
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Stimulate Human LINE-1 Retrotransposition

Abstract: L1 and Alu elements are among the most active retroposons (mobile elements) in the human genome. Several human diseases, including certain forms of breast cancer and leukemia, are associated with L1 and Alu insertions in functionally important areas of the genome. We present data demonstrating that environmental pollutants, such as heavy metals, can stimulate L1 retrotransposition in a tissue culture system using two different types of assays. The response to these agents was equivalent when using a cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…4,64,65 However, we have previously assessed the effect of several heavy metals on cell lines with a stable integration of the reporter plasmid. 35 Our data demonstrate that both assays yield equivalent results. Furthermore, nickel(II) has been reported to influence methylation and gene expression.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…4,64,65 However, we have previously assessed the effect of several heavy metals on cell lines with a stable integration of the reporter plasmid. 35 Our data demonstrate that both assays yield equivalent results. Furthermore, nickel(II) has been reported to influence methylation and gene expression.…”
Section: Discussionmentioning
confidence: 53%
“…A correction factor was utilized to compensate for the toxic effects of the heavy metals (evidenced as an overall loss of colony formation) when comparing the L1 retrotransposition to the control at different doses. 35 L1 retrotransposition increased with NiCl 2 dose, as reflected by the number of neo R colonies, peaking at about 2.5-fold at 150 μM NiCl 2 in comparison to the untreated (0 μM NiCl 2 ) control. This effect was not seen in cells exposed to CoCl 2 , which showed only decreased retrotransposition as cobalt dosage increased.…”
Section: Heavy Metals Have Differential Effects On Retrotranspositionmentioning
confidence: 95%
See 1 more Smart Citation
“…This increase in endogenous reverse transcriptase activity comes from L1 because it mediates retrotransposition of exogenous AluI element (25). In addition to compounds that damage DNA directly, several heavy metals, considered to be carcinogenic, also stimulate L1 retrotransposition in HeLa cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…Several bodies of evidence have shown that some carcinogens and a number of DNA-damaging agents, such as UV, benzo(a)pyrene (Lu et al 2000), cadmium, mercury, nickel (Kale et al 2005), a tryptophan photoproduct 6-formylindolo [3,2-b]carbazole (Okudaira et al 2010) and radiation (Farkash et al 2006) can stimulate retrotransposition in somatic cells.…”
Section: Introductionmentioning
confidence: 99%